Language, code, and platform-mediated textuality in electronic literature - Seroja Ainun Nadifah (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: Digital literary platforms have transformed literary production and reception by making language inseparable from code, interface, hyperlink, metadata, archive, and platform infrastructure. Objective: This study aims to examine how language, code, and textuality operate in electronic literature by focusing on selected works and records from the Electronic Literature Collection, ELMCIP Knowledge Base, The NEXT, IFDB, Interactive Fiction Archive, and Twine-based interactive fiction. Method: Using a qualitative interpretive design, the study combines Digital Discourse Analysis, Platform Studies, and Code/Textual Analysis to examine verbal units, hyperlinks, interface elements, metadata records, branching structures, navigational cues, and accessible code-related procedures. Results: The findings show that digital discourse organizes reading through commands, hyperlinks, menus, choices, metadata labels, and navigational cues that position readers as navigators, operators, assemblers, cartographers, and constrained agents. Implication: The findings also reveal that platforms and interfaces function as material conditions that classify, preserve, display, authorize, and regulate access to digital literary works through entry pages, metadata fields, emulator notes, file formats, browser layouts, and curatorial descriptions. Novelty: The novelty of this study lies in its integrated methodological framework, which treats electronic literature as a linguistic, procedural, infrastructural, and executable literary system rather than merely as digitized textual content.